2017
DOI: 10.1111/cogs.12478
|View full text |Cite
|
Sign up to set email alerts
|

A Multi‐Factor Account of Degrees of Awareness

Abstract: In this paper we argue that awareness comes in degrees, and we propose a novel multi-factor account that spans both subjective experiences and perceptual representations. At the subjective level, we argue that conscious experiences can be degraded by being fragmented, less salient, too generic, or flash-like. At the representational level, we identify corresponding features of perceptual representations-their availability for working memory, intensity, precision, and stability-and argue that the mechanisms tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 83 publications
4
50
0
Order By: Relevance
“…The Partial Awareness Hypothesis [23] argues that mental representations can be 'partial', and this explains what falsely can appear as a distinction between access and experience. Fazekas & Overgaard [43] suggest that consciousness (access as well as experience) can be degraded in different ways and suggest different mechanisms underlying this. These different theoretical proposals share, among other things, the idea that access and experience fundamentally go together as a principal thing.…”
Section: Discussionmentioning
confidence: 99%
“…The Partial Awareness Hypothesis [23] argues that mental representations can be 'partial', and this explains what falsely can appear as a distinction between access and experience. Fazekas & Overgaard [43] suggest that consciousness (access as well as experience) can be degraded in different ways and suggest different mechanisms underlying this. These different theoretical proposals share, among other things, the idea that access and experience fundamentally go together as a principal thing.…”
Section: Discussionmentioning
confidence: 99%
“…The term "global workspace" (Baars, 1988) or "global neuronal workspace" (Dehaene & Naccache, 2001) refers to a kind of central information exchange in the brain, subject to the limited capacity of working memory, but serving as a hub for the flow of information to or between specialized processors. The perceived present serves a similar function: There is no point in holding information if it is not to be potentially available to subsequent processing (Cleeremans, 2011;Farah, 1984;Fazekas & Overgaard, 2018). The kind of processing to which information in the perceived present might be available is a matter of conjecture.…”
Section: Perceptual Processes and Productsmentioning
confidence: 99%
“…in the form of various types of AMs-is being integrated into SAS. Recently, Fazekas & Overgaard [80] have published an extensive analysis of both cognitive and neural aspects of subjective experiences and perceptual representations. It is being demonstrated that both conscious experience and information at the representational level can be degraded along multiple dimensions.…”
Section: Implications For Consciousness and Cognitionmentioning
confidence: 99%
“…As described in the REFCON and REFGEN models, the level of AM integration is a crucial factor regarding the level of phenomenal consciousness. As phenomenal consciousness is interpreted as tied to availability, the situational and strategy-related interactions between SAS and GAS may not only influence the level of experienced consciousness but also qualitative factors such as those addressed by Fazekas & Overgaard [80]. In this way, according to the REF framework, phenomenal consciousness cannot 'overflow' availability of information for action [4,5].…”
Section: Access Consciousness and Phenomenal Consciousness In The Conmentioning
confidence: 99%